"India in a globalising world: some aspects of macroeconomy, agriculture and poverty" - Radhakrishna, R (ed.) (New Delhi, 2006)
Focusing on the current stage of India's development in the globalized world, this collection of essays by distinguished economists and scholars covers fiscal federalism, performance of firms, and macro modeling; agriculture issues such as land development and trade to small-farmer developments; and issues on poverty reduction, sustainable development, employment, and climate changes. The analysis presented in this volume provides research aimed at the construction of better policies to achieve growth and equity in India.
Keywords: Macroeconomics